2018
DOI: 10.1021/acs.molpharmaceut.8b00476
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Functionality and -Quality Lipids with RGD Peptide Ligands: Application for PEGylated Liposomes and Analysis of Intratumoral Distribution in a Murine Colon Cancer Model

Abstract: High-functionality and -quality (HFQ) lipids have a discrete molecular weight and good water dispersibility and can be produced by solid-phase peptide synthesis. Therefore, HFQ lipids are a promising material for the preparation of ligand-grafted PEGylated liposomes. Recently, we have reported serine-glycine repeated peptides ((SG) ) as a spacer of HFQ lipids and to substitute a conventional PEG spacer. We demonstrated the advantage of using (SG) spacers for peptide ligand presentation on the liposomal surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…The RGD-(SG)5-lipid was synthesized based on a solid phase peptide synthesis method [25]. The other inorganic chemicals were obtained from Nacalai Tesque (Kyoto, Japan).…”
Section: Materials and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RGD-(SG)5-lipid was synthesized based on a solid phase peptide synthesis method [25]. The other inorganic chemicals were obtained from Nacalai Tesque (Kyoto, Japan).…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…The encapsulation efficiency (EE) was calculated in accordance with the following equation: For the quantitation of the cellular association of DiD, a fluorescence-activated flow cytometer (LSRfortessa X-20, Becton Dickinson, USA) was used to detect the fluorescence. To study the mechanism of cellular association, RGD-modified liposomes (RLipo) were prepared in accordance with a previous report [25]. The cells were seeded in a 24-well plate at a density of intravenously injected via the tail vein every other day for five times.…”
Section: Drug Content and Encapsulation Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the intrapulmonary distribution of gene expression after inhalation is important information for therapeutic applications, it has not yet been elucidated in detail. Our group developed a multicolor deep imaging system using a tissue-clearing method and confocal microscopy in several organs [18][19][20][21]. We herein applied the tissue-clearing method to evaluate the intrapulmonary distribution of transgene expression using a multicolor deep imaging system for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have optimized a multicolor deep imaging system, by a tissue clearing method and confocal microscopy, in various organs [10][11][12][13]. Using this imaging system, we have revealed that pDNA can be delivered to peritubular fibroblast of renal cortex in suctioned kidney, after systemic injection in mice [10].…”
Section: Introductionmentioning
confidence: 99%